2014
DOI: 10.2131/jts.39.59
|View full text |Cite
|
Sign up to set email alerts
|

Retinal toxicity induced by small-molecule Hsp90 inhibitors in beagle dogs

Abstract: -Heat shock protein 90 (Hsp90) is a constitutively expressed molecular chaperone and plays an important role in the folding of client proteins with key regulatory roles in growth, survival, differentiation and metastasis. Because inhibition of Hsp90 degrades multiple oncogenic client proteins, it is considered to be an attractive anticancer therapy, and clinical trials of several Hsp90 inhibitors have been carried out. In the present study, two structurally distinct Hsp90 inhibitors, CH5164840 and CH5449302, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
(26 reference statements)
1
25
0
Order By: Relevance
“…HSP90 plays a critical role also in retinal function, and sustained HSP90 inhibition may be associated with eye disorders (19)(20)(21). Effects of TAS-116 on retina have yet to been examined; it was reported that reduction of rhodopsin kinase (GRK1), one of HSP90 client proteins, by sustained HSP90 inhibition adversely affects visual function (22).…”
Section: Discussionmentioning
confidence: 99%
“…HSP90 plays a critical role also in retinal function, and sustained HSP90 inhibition may be associated with eye disorders (19)(20)(21). Effects of TAS-116 on retina have yet to been examined; it was reported that reduction of rhodopsin kinase (GRK1), one of HSP90 client proteins, by sustained HSP90 inhibition adversely affects visual function (22).…”
Section: Discussionmentioning
confidence: 99%
“…To target the epichaperome in clinic, inhibitors that discriminate between a single chaperome and a chaperome incorporated into epichaperomes (that is HSP90 versus HSP90-containing epichaperomes for example) are preferred for treatment as they may offer better target engagement and a safer profile (22,46). Although acute chaperome inhibition may not be toxic to normal cells, chronic suppression may have unwanted effects (107,108). A number of review articles have been written on the discovery, identity, and mode of action of small molecule inhibitors of HSP90, HSP70, and others (62, 109 -117), and the reader is referred to these sources for further expansion on this topic.…”
Section: Epichaperome As a Tumor Target And Biomarkermentioning
confidence: 99%
“…A previous study reported a Parkinson's disease-like syndrome in rats treated with deguelin at high doses (Caboni et al, 2004). In addition, it was reported that Hsp90 inhibitors may induce ocular toxicity (Kanamaru et al, 2014). Although it is not clear whether therapeutic doses of deguelin would induce the side effects and whether the side effects can be relieved after drug withdrawal, the potential toxicities of deguelin can be a considerable obstacle to its clinical use.…”
Section: Introductionmentioning
confidence: 99%